Cattle make two‐stage discriminations in patch choice. Issue 2 (30th December 2014) - Hirata, Masahiko; Tajiri, Yuko; Murakami, Kozue; Ikeda, Kazuki; Oka, Kanako; Tobisa, Manabu
Abstract: Discrimination among vegetation patches differing in quantity and quality is crucial to the foraging success of grazing animals living in grasslands. Animals are assumed to discriminate preferred patches from others first, before they visit patches to eat, and then when they are eating patches. We conducted six experiments to test the ability of cattle ( Bos taurus ) to discriminate among vegetation patches at these two stages during foraging. In each experiment, a group of Japanese Black cows was allowed to graze a tropical grass ( Paspalum notatum ) for 30 min in a 20 × 20 m area comprising 4, 6 or 9 types of patches. Animals almost always visited and grazed the patches selectively, with a longer residence (grazing) time per visit in more frequently visited patches. Allocation of grazing time was correlated more closely with allocation of visits than with residence time per visit. Faced with patchy vegetation, cattle can discriminate preferred patches from less‐preferred and non‐preferred patches at two stages during foraging. The first‐stage discrimination (pre‐visit‐and‐eating discrimination) is more important than the second (eating discrimination) as a determinant of grazing time allocation to patches.